TAVI and the future of aortic valve replacement. Issue 12 (10th October 2019) - Howard, Callum; Jullian, Lucas; Joshi, Mihika; Noshirwani, Arish; Bashir , Mohamad; Harky, Amer
Abstract: Aortic valve stenosis (AS) is the most common valvular pathology and has traditionally been managed using surgical aortic valve replacement (SAVR). A large proportion of affected patient demographics, however, are unfit to undergo major surgery given underlying comorbidities. Since its introduction in 2002, transcatheter aortic valve implantation (TAVI) has gained popularity and transformed the care available to different‐risk group patients with severe symptomatic AS. Specific qualifying criteria and refinement of TAVI techniques are fundamental in determining successful outcomes for intervention. Given the successful applicability in high‐risk patients, TAVI has been further developed and trialed in intermediate and low‐risk patients. Within intermediate‐risk patient groups, TAVI was shown to be noninferior to SAVR evaluating 30‐d mortality and secondary endpoints such as the risk of bleeding, development of acute kidney injury, and length of admission. The feasibility of expanding TAVI procedures into low‐risk patients is still a controversial topic in the literature. A number of trials have recently been published which demonstrate TAVI as noninferior and even superior over SAVR for primary study endpoints.